PENGEMBANGAN MODEL PEMBELAJARAN GUIDED PROJECT BASED LEARNING (PJBL) INTEGRATED CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MEMPERKUAT KARAKTER PESERTA DIDIK PADA PEMBELAJARAN PENJASORKES DI SMA - Mulyanti Mulyanti (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
Increased delinquency of students such as smoking, gambling, learning to be unfocused, not respecting educators, parents, friends and others encourages speakers to develop Integrated Contextual Teaching and Learning (CTL) Guided Project Based Learning Model to Strengthen Student Character Penjasorkes learning in high school. This paper consists of abstracts, introductions, discussions and conclusions. The results expected in this paper are the Integrated Contextual Teaching and Learning (CTL) Learning Model Guided Project Based Learning to Strengthen Student Character on Penjasorkes Learning in High School. The conclusion of this paper shows that the Integrated Contextual Teaching and Learning Guided Project Based Learning (CTL) model can strengthen the character of students in Penjasorkes learning in high school. Keywords